2019
DOI: 10.2308/accr-52522
|View full text |Cite
|
Sign up to set email alerts
|

Do Firms That Have a Common Signing Auditor Exhibit Higher Earnings Comparability?

Abstract: We hypothesize that if individual auditors possess unique audit styles that they consistently apply to different audit engagements, then client firms with a common signing auditor will exhibit higher earnings comparability. Using a large sample of Chinese firms, we find that client firms report more comparable earnings when they are audited by the same individual auditor than when they are audited by (1) different audit firms, (2) the same audit firm, but different audit offices, and (3) the same audit office,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 40 publications
11
88
4
1
Order By: Relevance
“…To understand whether two CPAs are simultaneously responsible or whether the dual-signature requirement has created an impact of DME on CGES, the Public Company Accounting Oversight Board (2009) identified that a signature of a CPA on an audit report may help increase accountability and transparency. Since 1983, Taiwan has required that financial statements filed with the Public Issuance Division must be audited by two CPAs and signed to certify the financial statements with jointly guaranteed responsibility (Chen et al 2020). First, the empirical results in Table 6 shows that the DME estimation coefficient is 0.1675 (z = 4.24, p < 0.01), reaching a significant level of 1%.…”
Section: Cges and Dme: Change Lead Cpa And Change Concurring Cpamentioning
confidence: 98%
“…To understand whether two CPAs are simultaneously responsible or whether the dual-signature requirement has created an impact of DME on CGES, the Public Company Accounting Oversight Board (2009) identified that a signature of a CPA on an audit report may help increase accountability and transparency. Since 1983, Taiwan has required that financial statements filed with the Public Issuance Division must be audited by two CPAs and signed to certify the financial statements with jointly guaranteed responsibility (Chen et al 2020). First, the empirical results in Table 6 shows that the DME estimation coefficient is 0.1675 (z = 4.24, p < 0.01), reaching a significant level of 1%.…”
Section: Cges and Dme: Change Lead Cpa And Change Concurring Cpamentioning
confidence: 98%
“…However, there is some audit literature that has focused on the role of audit in enhancing the quality of financial statements in terms of increasing the financial statements' comparability. In this context, prior research (Francis et al, 2014;Kawada, 2014;Mohseni et al, 2014) has agreed that firms that are audited by the same audit firm have greater comparable earnings, similarly if being audited by the same auditor (e.g., Chen et al, 2020;Jiu et al, 2020).…”
Section: Audit Style and Firm-pair Earnings Comparabilitymentioning
confidence: 99%
“…Regarding the determinants of the financial statements' comparability, prior studies have focused on the adoption of IFRS (e.g., Barth et al, 2012;Brochet et al, 2013;DeFond et al, 2011;Lin et al, 2019), the effectiveness of the audit committee (e.g., Endrawes et al, 2020), and the audit style (e.g., Cao et al, 2016;Chen et al, 2020;Francis et al, 2014;Jiu et al, 2020;Kawada, 2014). Audit style means that each audit firm has its own internally developed working rules that interpret the accounting and auditing standards and guide its auditors when implementing the audit process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations